STABLE HYDROGEN ISOTOPES IN IRON OXIDES: III. NONSTOICHIOMETRIC HYDROGEN IN GOETHITE - Yapp C.J.; Poths H. (My University, 1995)
Hydrogen isotope exchange experiments between goethite and water vapor were performed at 22°C after vacuum ''outgassing'' at temperatures ranging from 100 to 140°C. The results for five natural and one synthetic goethite can be most simply interpreted in terms of two hydrogen reservoirs in the mineral. One reservoir is stoichiometric, structural hydroxyl hydrogen (FeOOH) which does not seem to exchange at 22°C on the timescales of these experiments. The other reservoir, as indicated by chemical analyses, appears to be nonstoichiometric hydrogen which persists in the sample even after outgassing at 100 to 140°C. This ''high temperature'' nonstoichiometric (HTN) hydrogen rapidly exchanges isotopes with water vapor at 22°C and seems to have reached, or closely approached, exchange equilibrium after only 15 to 17 hours. The isotopic fractionation factor (αe-v) between the HTN hydrogen and water vapor is estimated to be about 0.996 at 22°C. The exchange experiments indicate that the D ratio of stoichiometric hydrogen is not changed by the procedure for outgassing at 100 to 140°C. The amount of HTN hydrogen ranges from nearly zero to about 20% of the total hydrogen among these samples. When present in higher proportions, exchange experiments of the type described here may be necessary to determine the δD value of structural OH in goethite. However, outgassing at about 100°C in vacuum prior to dehydration at 850°C appears to be sufficient for measurement of δD values of structural OH in many natural goethites.